Quality Assurance Scheme of Undergraduate Medical Education in Medical Colleges of Bangladesh: Past, Present and Future - Nurunnabi, Abu Sadat Mohammad; Parvin, Shamima; Rahim, Riffat; Begum, Munira; Ghosh, Subrata; Sweety, Afroza Akbar; Sultana, Dahlia; Jahan, Neelima; Muqueet, Md Abdul; Islam, Md Mozaharul (Mugda Medical College Journal, 2023)
Improving quality of medical education is a key contributing factor to improving the quality of healthcare. The rapid increase in number of medical colleges in Bangladesh, especially in the private sector, makes its vital to have effective quality assurance system in place. Quality assurance resembles a state in which medical colleges take on challenges to address different aspects of quality in undergraduate medical education through check and balance in a methodical approach. In 1998, the World Health Organization (WHO) supported the Center for Medical Education (CME) and the Directorate General of Health Service (DGHS) to develop and publish the National Guidelines & Tools for the Quality Assurance Scheme (QAS) for medical colleges in Bangladesh. Since then that guideline has been serving as resource material and guide for institutionalization of the QAS based on the three principles of accountability, self-evaluation, and external peer review, with the latest revision done in 2012. At the institutional level, the scheme was proposed to be managed by the Academic Council, Academic Coordination Committee, the four (previously three) Phase Coordination Groups, Subject Coordinators, and Faculty Review & Development Committee. The operational framework is based on course appraisal, faculty development and review scheme and external review. A model of “pair of medical colleges” was also proposed as to oversee the QAS activities of each other and report to the National Quality Assurance Body (NQAB). This review paper aims to highlight the history of QAS in our medical colleges, their achievements to date and challenges as well as scopes for future improvement to enhance the quality of medical education in Bangladesh. Mugda Med Coll J. 2022; 5(2): 104-109